Stella Louella's runaway book - Ernst, Lisa Campbell (New York : Simon & Schuster Books for Young Readers, 1998)
As she tries to find the book that she must return to the library that day, Stella gathers a growing group of people who have all enjoyed reading the book.
Keywords: Books and reading -- Fiction; Lost and found possessions -- Fiction; Librarians -- Fiction